MANAJEMEN PENGELOLAAN ZAKAT YANG EFEKTIF DI ERA KONTEMPORER (UIN Sunan Kudus, 2015)
This article describes the management of zakat in the contemporary era. The author began with 1) the concept of zakat in Islam that includes understanding and assorted well as scholarly opinion ‘about it. The scholars argue that zakat is a wealth of content assets that meet the minimum requirements (nishab) and Waku span of one year (haul) the rights and given to mustahiq (recipients). Also discussed 2) of zakat profession, namely zakat imposed pda each job tau professional expertise, whether done alone or shared with the people or institutions, which bring in income (money) that meets the Nisab (the minimum threshold to be able to pay zakat . 3) the core of this article describes the management of zakat which is considered essential to the welfare of the Muslims, then zakat must be properly managed gnats can gain the trust of the community. In managing zakat can be through management. Zakat management-based management can be done with the basic assumption that all activities associated with the charity carried out in a professional manner. Zakat management in a professional manner, needs to be done with the interrelations between the various activities associated with the charity. 4) at the end of the building described in managing zakat management by using the theory of James Stoner. The management model includes the planning process (planning), organizing (organizing), direction (actuating) and supervision (controlling). Stoner’s fourth model can be applied in any activity with the concept of socialization zakat management, collection, utilization and supervision.